The association of heavy metals/metalloid and stroke—Findings in Shanxi, China and the US NHANES from 2011 to 2020 - Yuese Yuan; Li Zhang; Fuying Liu; Haobo Liu; Ying Wang; Xiujuan Yang; Liangpo Liu; Ben Li; Li Wang; Jin Yang; Hongyan Cao; Yulan Qiu; et al. (Ecotoxicology and Environmental Safety)
Background: Previous studies provided contradictory evidence regarding the relationship between metal concentrations and ischemic stroke (IS). Methods: A total of 100 adults with IS were included in this study, as well as an equal number of controls. Inductively coupled plasma-mass was used to measure metals’ concentrations in whole blood and plasma. In order to identify metals that were associated with IS, we applied principal component analysis (PCA) and principal component (PC) regression. Finally, we included 3867 participants from the US National Health and Nutrition Examination Survey (NHANES) 2011–2020 to estimate the association between urine tin (Sn) and stroke with logistic regression and COX proportional hazard models. Results: The fourth PC, characterized by copper (Cu) and Sn in whole blood, was associated with a higher risk of IS (OR=19.43, 95 %CI: 4.25, 88.89 for the highest quartile vs. the lowest quartile). A higher risk of IS was linked to the second PC, characterized by Sn, aluminum (Al), titanium (Ti), nickel (Ni) in plasma (OR= 12.85, 95 %CI: 3.91, 42.26 for the highest quartile vs. the lowest quartile). For NHANES, Sn was associated with a higher risk of stroke (OR= 1.69, 95 %CI: 1.07, 2.66 for the highest quartile vs. the lowest quartile). There was no significant relationship between urine Sn and all-cause deaths. Conclusion: In this research, the exposures of Sn, Cu, Al, Ti, and Ni were associated with IS. Specifically, the relationship between Sn and the risk of stroke has been established among both Chinese and US participants.